Characteristics of volcanic ash soils of southern area of Mount Ruapehu, North Island, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Soil Science at Massey University - Suryaningtyas, Dyah Tjahyandari (Massey University, 1998)
Geochemical and pedological properties of five volcanic soils were examined to characterise the effects of weathering. The five soils studied are from the southern area of Mount Ruapehu, New Zealand. The principal parent materials are rhyolitic and andesitic tephras. Soils examined in this study are characterised by thick and dark A horizons, crumb and nut structure, and sandy to clay texture. All pedons contain allophane, mostly as Al-rich allophane with Al:Si ratio ≅ 2.0. Mineralogical analysis data demonstrate the differences in parent materials, including quartz, plagioclase feldspar, hypersthene, augite, hornblende and magnetite. Halloysite and kaolinite are also present in the soils. When allophane is the dominant material in the clay fraction, the chemical properties are characterised by accumulation of humus, high fluoride pH and high phosphate retention. State factors of soil formation are reviewed and discussed. This study reveals that weathering processes are key determinants of site-specific environmental conditions, whereas compositional factors, including tephra age, may determine A1 behaviour, and control the concentration of A1 in soil solution and its distribution throughout the profile. Four soils meet the andic criteria and qualify for the Andisols order. They are: Typic Udivitrand, ashy, isofrigid; Typic Hapludand, medial, isofrigid; Typic Hydrudand, hydrous, isofrigid; and Hydric Endoaquand, medial, isofrigid. Another soil is under the Entisols order and is classified as Vitrandic Udifluvent, sandy, mixed, isofrigid. The Andisols are correlated with Allophanic Soils in the New Zealand Soil Classification. The complete classification is: vitric Orthic Allophanic Soil, vitric Orthic Allophanic Soil, typic Orthic Allophanic Soil, and typic Impeded Allophanic Soil. The Vitrandic Udifluvent is correlated with typic Orthic Pumice Soil.
Keywords: Andosols; Mount Ruapehu